Dual-ligand modified liposomes provide effective local targeted delivery of lung-cancer drug by antibody and tumor lineage-homing cell-penetrating peptide. (1st January 2018) - Lin, Congcong; Zhang, Xue; Chen, Hubiao; Bian, Zhaoxiang; Zhang, Ge; Riaz, Muhammad Kashif; Tyagi, Deependra; Lin, Ge; Zhang, Yanbo; Wang, Jinjin; Lu, Aiping; Yang, Zhijun
Abstract: The abilities of a drug delivery system to target and penetrate tumor masses are key factors in determining the system's chemotherapeutic efficacy. Here, we explored the utility of an anti-carbonic anhydrase IX (anti-CA IX) antibody and CPP33 dual-ligand modified triptolide-loaded liposomes (dl-TPL-lip) to simultaneously enhance the tumor-specific targeting and increase tumor cell penetration of TPL. In vitro, the dl-TPL-lip increased the cytotoxicity of TPL in CA IX-positive lung cancer cells, which showed tunable size (137.6 ± 0.8 nm), high-encapsulation efficiency (86.3 ± 2.6%) and sustained release. Dl-TPL-lip significantly improved the ability of liposomes to penetrate 3 D tumor spheroids and exhibited a superior inhibiting effect. Furthermore, pharmacokinetic studies in rats that received TPL liposomal formulations by endotracheal administration showed a reduced concentration of TPL (17.3%–30.6% compared to free TPL) in systemic circulation. After pulmonary administration in orthotopic lung tumor-bearing mice, dl-TPL-lip significantly enhanced TPL anti-cancer efficacy without apparent systemic toxicity. This dual-ligand modified liposomal vehicle presents a potential system for localized and targeted delivery of anti-cancer drugs to improve their efficacy.